2020
DOI: 10.1007/s42764-020-00021-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transcription-mediated replication stress on genome instability and human disease

Abstract: DNA replication is a vital process in all living organisms. At each cell division, > 30,000 replication origins are activated in a coordinated manner to ensure the duplication of > 6 billion base pairs of the human genome. During differentiation and development, this program must adapt to changes in chromatin organization and gene transcription: its deregulation can challenge genome stability, which is a leading cause of many diseases including cancers and neurological disorders. Over the past decade, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 254 publications
(291 reference statements)
0
11
0
Order By: Relevance
“…This replication stress (RS) represents an important cause of genomic instability, and strong evidence in recent years indicates that oncogene-induced RS is a major driver of carcinogenesis and tumor progression. 1 The transcription and replication machineries share the same DNA template, which renders head-on (HO) or codirectional (CD) collisions inevitable. HO collisions are considered as more deleterious to the genomic stability.…”
Section: Author's Viewmentioning
confidence: 99%
See 3 more Smart Citations
“…This replication stress (RS) represents an important cause of genomic instability, and strong evidence in recent years indicates that oncogene-induced RS is a major driver of carcinogenesis and tumor progression. 1 The transcription and replication machineries share the same DNA template, which renders head-on (HO) or codirectional (CD) collisions inevitable. HO collisions are considered as more deleterious to the genomic stability.…”
Section: Author's Viewmentioning
confidence: 99%
“…3 R-loops have been proposed to play both positive and negative roles in gene expression and other chromosome functions. 1,3 Many factors have been identified to prevent the formation of R-loops or remove them. These include RNA splicing factors, DNA topoisomerases, RNase H and specialized RNA:DNA helicases.…”
Section: Author's Viewmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell-type specific program that regulates the progression of DNA replication during the synthesis phase (S phase) is referred to as replication timing (RT) program 10,11 . It has been reported that RT is altered throughout disease development, such as in cancers and neurological disorders [12][13][14] . In addition, RT has been shown, by others and us, to play an important role in shaping the mutational landscape and impacting genome stability in both normal and cancer cells [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%